The relationship between velocity utilization rate and pole vault performance - Yang, M.-H.; Chen, C.-C.; Ho, W.-H.; Hsu, C.-T. (Journal of Human Sport & Exercise, 2021)
In the pole vault event, the velocity of approach is a highly vital factor. As velocity of approach improvements highly impact performance improvements. This study analysed the relationships between sprint running`s speed (SR), pole running (PR, without jump), and the pole vault approach (PVA, with real jump). Analysed too were the relationships between both the approach and performance`s respective running distance, velocity, and velocity utilization rates. Methods: Ten male pole vaulters were recruited. Measured was each 5-meter segment`s average velocity of his respective SR, PR, and PVA, along with the distance to maximum velocity. Results: The maximum average velocity of the PR`s 5m segments altogether was significantly positively correlated with pole vault (PV) performance; The maximum average velocity of the PR`s 5m segments altogether was significantly positively correlated with the last 5m PVA average velocity; The PVA velocity`s utilization rate was significantly negatively correlated with the difference between the distance to the PR`s maximum velocity and the PVA`s distance. Conclusion: The PR segment`s maximum speed capability can evaluate both a pole vaulter`s potential and pole vault-specific abilities. This study`s recruited pole vaulters` respective approach distances were generally insufficient that resulted in a lower velocity utilization rate. Suggested is that in training, the pole vaulter could first find the distance required to reach the highest velocity upon starting from the PR test. Thus, this subsequently known distance could be applied in tandem with the pole vault`s approach to both improve the PVA`s utilization rate and reach the individual highest speed level.